Improved ROS defense in the swimbladder of a facultative air-breathing erythrinid fish, jeju, compared to a non-air-breathing close relative, traira - Pelster, Bernd; Giacomin, Marina Mussoi; Wood, Chris M.; Val, Adalberto Luis (Journal of Comparative Physiology B: Biochemical, Systemic, and Environmental Physiology, 2016)
The jeju Hoplerythrinus unitaeniatus and the traira Hoplias malabaricus are two closely related erythrinid fish, both possessing a two-chambered physostomous swimbladder. In the jeju the anterior section of the posterior bladder is highly vascularized and the swimbladder is used for aerial respiration; the traira, in turn, is a water-breather that uses the swimbladder as a buoyancy organ and not for aerial oxygen uptake. Observation of the breathing behavior under different levels of water oxygenation revealed that the traira started aquatic surface respiration only under severe hypoxic conditions and did not breathe air. In the jeju air-breathing behavior was observed under normoxic conditions, and the frequency of air-breathing was significantly increased under hypoxic conditions. Unexpectedly, even under hyperoxic conditions (30 mg O2 L−1) the jeju continued to take air breaths, and compared with normoxic conditions the frequency was not reduced. Because the frequently air-exposed swimbladder tissue faces higher oxygen partial pressures than normally experienced by other fish tissues, it was hypothesized that in the facultative air-breathing jeju, swimbladder tissue would have a higher antioxidative capacity than the swimbladder tissue of the water breathing traira. Measurement of total glutathione (GSSG/GSH) concentration in anterior and posterior swimbladder tissue revealed a higher concentration of this antioxidant in swimbladder tissue as compared to muscle tissue in the jeju. Furthermore, the GSSG/GSH concentration in jeju tissues was significantly higher than in traira tissues. Similarly, activities of enzymes involved in the breakdown of reactive oxygen species were significantly higher in the jeju swimbladder as compared to the traira swimbladder. The results show that the jeju, using the swimbladder as an additional breathing organ, has an enhanced antioxidative capacity in the swimbladder as compared to the traira, using the swimbladder only as a buoyancy organ. © 2016, The Author(s).
Keywords: Fish Protein; Glutathione; Glutathione Disulfide; Oxidoreductase; Reactive Oxygen Metabolite; Air; Air Sac; Animals; Characiformes; Metabolism; Muscle; Physiology; Respiratory Function; Air; Air Sacs; Animal; Characiformes; Fish Proteins; Glutathione; Glutathione Disulfide; Muscles; Oxidoreductases; Reactive Oxygen Species; Respiratory Physiological Phenomena